(1S,2S)-2-(1-{ 2-(2-Oxidobenzylideneamino)cyclohexyl imino}-ethyl)pheno lato-kappa O-4,N,N ',O ' copper(II) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
In the title compound, [Cu(C21H22N2O2)], the cyclohexyl ring adopts a chair conformation with the two imine groups linked at equatorial positions. The CuII ion is coordinated by two N atoms and two O atoms from the bis-Schiff base ligand in a slightly distorted square-planar geometry. The dihedral angle between the two benzene rings is 45.89 (9)°. The crystal structure is devoid of any classical hydrogen bonds. However, intermolecular C-H...O interactions are present and stabilize the structure.